Low immunogenicity of tocilizumab in patients with rheumatoid arthritis. Issue 6 (22nd December 2016) - Burmester, Gerd R; Choy, Ernest; Kivitz, Alan; Ogata, Atsushi; Bao, Min; Nomura, Akira; Lacey, Stuart; Pei, Jinglan; Reiss, William; Pethoe-Schramm, Attila; Mallalieu, Navita L; Wallace, Thomas; et al.
Abstract : Objective: Subcutaneous (SC) and intravenous formulations of tocilizumab (TCZ) are available for the treatment of patients with rheumatoid arthritis (RA), based on the efficacy and safety observed in clinical trials. Anti-TCZ antibody development and its impact on safety and efficacy were evaluated in adult patients with RA treated with intravenous TCZ (TCZ-IV) or TCZ-SC as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs). Methods: Data from 5 TCZ-SC and 8 TCZ-IV phase III clinical trials and 1 TCZ-IV clinical pharmacology safety study (>50 000 samples) were pooled to assess the immunogenicity profile of TCZ-SC and TCZ-IV (8974 total patients). The analysis included antidrug antibody (ADA) measurement following TCZ-SC or TCZ-IV treatment as monotherapy or in combination with csDMARDs, after dosing interruptions or in TCZ-washout samples, and the correlation of ADAs with clinical response, adverse events or pharmacokinetics (PK). Results: The proportion of patients who developed ADAs following TCZ-SC or TCZ-IV treatment was 1.5% and 1.2%, respectively. ADA development was also comparable between patients who received TCZ monotherapy and those who received concomitant csDMARDs (0.7–2.0%). ADA development did not correlate with PK or safety events, including anaphylaxis, hypersensitivity or injection-site reactions, and no patients who developed ADAs had loss of efficacy. Conclusions: The immunogenicity risk of TCZ-SC and TCZ-IV treatment was low, either as monotherapy or in combination with csDMARDs. Anti-TCZ antibodies developed among the small proportion of patients had no evident impact on PK, efficacy or safety.